Real-time finite element structural analysis in augmented reality. (September 2015) - Huang, J.M.; Ong, S.K.; Nee, A.Y.C.
Highlights: An integrated platform for performing real-time FEA simulations in AR. AR visualization of FEA solutions and a tangible interface for enhanced data exploration. AR-assisted configuration of wireless sensor network to acquire loads onsite for FEA. Abstract: Conventional finite element analysis (FEA) is usually carried out in offsite and virtual environments, i.e., computer-generated graphics, which does not promote a user's perception and interaction, and limits its applications. With the purpose of enhancing structural analysis with augmented reality (AR) technologies, the paper presents a system which integrates sensor measurement and real-time FEA simulation into an AR-based environment. By incorporating scientific visualization technologies, this system superimposes FEA results directly on real-world objects, and provides intuitive interfaces for enhanced data exploration. A wireless sensor network has been integrated into the system to acquire spatially distributed loads, and a method to register the sensors onsite has been developed. Real-time FEA methods are employed to generate fast solutions in response to load variations. As a case study, this system is applied to monitor the stresses of a step ladder under actual loading conditions. The relationships among accuracy, mesh resolution and frame rate are investigated.